Certificate No. 00003 - Alimardonov , Ilxom (Innovation Science and Technology, 2025)
This certificate confirms that Professor Alimardonov Ilxom Muzrabshoxovich, Doctor of Economic Sciences (DSc), is a member of the Editorial Board of the scientific journal "INNOVATION SCIENCE AND TECHNOLOGY", which specializes in science and technology as well as economic innovations. THE SCIENTIFIC POPULAR ELECTRONIC JOURNAL "INNOVATION SCIENCE AND TECHNOLOGY HAS BEEN REGISTERED UNDER THE NUMBER C-5669633 BY THE AGENCY FOR INFORMATION AND MASS COMMUNICATIONS (AOKA) OF THE REPUBLIC OF UZBEKISTAN, EFFECTIVE FROM OCTOBER 9. 2024 The soentific electronic joumal "Innovation Science and Technology has been included in the list of scientific publications recommended for the publication of main scientific results of dissertations for the award of PhD and DSc degrees in economics and technical sciences, in accordance with the Resolution No. 370 of the Presidium of the Higher Attestation Commission of the Republic of Uzbekistan, dated May 8. 2025.